Compterosmittia wangi sp. nov. from Oriental China (Diptera, Chironomidae) - Zhou, Xu-Shen; Fang, Da-Zhou; Gao, Rui; Wang, Ying; Yan, Chun-Cai; Liu, Wen-Bin (Zootaxa, 2022)
A new species, Compterosmittia wangi Liu sp. nov. is described and illustrated as adult males. An updated key to males of Compterosmittia worldwide is presented.